2023
DOI: 10.1186/s40543-023-00377-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteome network analysis of skeletal muscle in lignan-enriched nutmeg extract-fed aged mice

Abstract: Sarcopenia, characterized by reduced muscle mass and fiber number leading to muscular atrophy, has been associated with serious socioeconomic challenges among the elderly in developed countries. Therefore, preventing sarcopenia could be a promising strategy for achieving a healthy aging society. Nutmeg (Myristica fragrans) has been used as a spice to increase flavor and prevent putrefaction of food. Nutmeg contains various bioactive components that improve muscle activity. To determine the potential effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, actin was downregulated by exercise fatigue in rat skeletal muscle . Lee et al . found the supplement of lignan-rich nutmeg extract upregulated the Acta1 expression in muscle tissue of aged mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, actin was downregulated by exercise fatigue in rat skeletal muscle . Lee et al . found the supplement of lignan-rich nutmeg extract upregulated the Acta1 expression in muscle tissue of aged mice.…”
Section: Resultsmentioning
confidence: 99%
“…35 Moreover, actin was downregulated by exercise fatigue in rat skeletal muscle. 16 Lee et al 36 found the supplement of lignan-rich nutmeg extract upregulated the Acta1 expression in muscle tissue of aged mice. Thus, YPLP contributed to the generation of muscle protein, thereby maintaining the muscle structure and tolerance.…”
Section: Analysis Of Daps Between H-yplp and Nc Groups The Informatio...mentioning
confidence: 99%
“…These findings illustrated that the nutmeg extraction method for concentrating bioactive lignan compounds, while removing toxic substances, has great potential for the treatment of various metabolic diseases. In previous studies, the authors prepared lignan-enriched nutmeg extract (LNX), which would comprise minimal levels of toxic myristicin (<0.5%) and maximum nectandrin B ( 28 ) and reported that LNX restores muscle proteins in aged mice ( 30 ), suggesting the potential of LNX as a therapeutic agent to overcome sarcopenia. However, the anti-obesity (antiadipogenic, prolipolytic and anti-inflammatory) effects of LNX on preadipocytes remain unclear.…”
Section: Introductionmentioning
confidence: 99%